2016
DOI: 10.11604/pamj.2016.25.109.6873
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with late antenatal care booking: population based observations from the 2007 Zambia demographic and health survey

Abstract: IntroductionIn spite of the extreme importance of an early antenatal care visit, more than 50% of Zambian pregnant women book for antenatal care late. We aimed to determine factors associated with late antenatal care booking in Zambia.MethodsData stem from the 2007 Zambia Demographic and Health Survey where information on socio-demographic, social-economic, obstetrical characteristics and timing of the first antenatal visit were extracted on all women aged 15 to 49 years. A weighted survey analysis using STATA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
47
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 19 publications
20
47
3
3
Order By: Relevance
“…Our finding that multiparity is an independent predictor of late antenatal booking is consistent with other settings where it has been documented that women view no advantages to early booking because antenatal care is seen as primarily curative and not preventative, or in places where care quality is poor or expensive . Similarly, our finding that unintended pregnancy is an independent predictor of late antenatal booking is consistent with other studies, which have shown that women with an unintended pregnancy are 2.0–4.4 times more likely to attend their booking visit late . Antenatal care in the Solomons could be strengthened by improving the quality of services provided as recommended by the WHO in their document on antenatal care for a positive pregnancy experience .…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that multiparity is an independent predictor of late antenatal booking is consistent with other settings where it has been documented that women view no advantages to early booking because antenatal care is seen as primarily curative and not preventative, or in places where care quality is poor or expensive . Similarly, our finding that unintended pregnancy is an independent predictor of late antenatal booking is consistent with other studies, which have shown that women with an unintended pregnancy are 2.0–4.4 times more likely to attend their booking visit late . Antenatal care in the Solomons could be strengthened by improving the quality of services provided as recommended by the WHO in their document on antenatal care for a positive pregnancy experience .…”
Section: Discussionsupporting
confidence: 91%
“…Un total de 116 de las 391 participantes ( [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]9), y una razón cruda de prevalencias (RP) de 2,53 (IC 95 %: 1,64-3,91). Otros factores de riesgo asociados al inicio tardío en el análisis bivariado fueron la edad, la escolaridad menor a 12 años y la no afiliación al SGSSS.…”
Section: Resultsunclassified
“…De otro lado, tener una relación estable disminuye la probabilidad de iniciar tardíamente la APN. Contrario a nuestros hallazgos, la asociación entre unión estable e inicio tardío ha sido reportada por otros estudios (6,7).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Our study found out that women who had unplanned pregnancies were less likely to utilize maternal health services. Two studies in east Africa also found out that women who had unplanned pregnancies were two times more likely to book for ANC late compared to women who had planned to have a baby [40,41]. This may be attributed to the late diagnosis of the pregnancy thus, the woman may be shy visit the clinic and register the pregnancy especially in cases where the pregnant mother is very young, dependent, and not married.…”
Section: Discussionmentioning
confidence: 99%